2012
DOI: 10.3892/etm.2012.546
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 119 cases of pediatric acute promyelocytic leukemia: Comparisons of four treatment regimes

Abstract: Abstract. Clinical trials have demonstrated that pediatric acute promyelocytic leukemia (APL) is highly curable. Small-scale studies have reported on the treatment of APL using one or two treatment regimes. Here, we report a multiple center-based study of 119 cases of pediatric APL treated with four regimes based on all-trans-retinoic acid (ATRA). We retrospectively analyzed the clinical characteristics, laboratorial test results and treatment outcome of the pediatric APL patients. Regime 1 used an in-house de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We identified a total of 838 articles from PubMed; after removing duplicates and non-English studies, 591 titles and abstracts were screened, resulting in the exclusion of 434 articles ( Figure 1 ). In addition to the remaining 157 full-text articles, we further identified 57 articles [ 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…We identified a total of 838 articles from PubMed; after removing duplicates and non-English studies, 591 titles and abstracts were screened, resulting in the exclusion of 434 articles ( Figure 1 ). In addition to the remaining 157 full-text articles, we further identified 57 articles [ 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…In the 1980s, a famous Chinese medical expert in China, Doctor Shi-lin Huang, designed a Realgar-Indigo naturalis formula (RIF), in which, realgar, a mined ore, is the principal element and Indigo naturalis, Salvia miltiorrhiza, and Radix psudostellariae are adjuvant components to assist the effects of realgar. The main components of RIF are realgar, Indigo naturalis, and Salvia miltiorrhiza, with tetraarsenic tetrasulfide (A), indirubin (I), and tanshinone IIA (T) as major active ingredients, respectively [1214]. Multicenter clinical trials showed that a complete remission rate of 96.7% [15] to 98% [16] and a 5-year overall survival rate of 86.88% [17] were achieved in APL patients receiving RIF, with moderate adverse effects such as gastrointestinal discomfort and rash.…”
Section: The Part Ahead Of Modern Medicine Involuntarilymentioning
confidence: 99%